Risk, Returns, and Multinational Production * - Fillat, José L.; Garetto, Stefania (Quarterly Journal of Economics, 2015)
Abstract This article starts by unveiling a strong empirical regularity: multinational corporations exhibit higher stock market returns and earning yields than nonmultinational firms. Within nonmultinationals, exporters exhibit higher earning yields and returns than firms selling only in their domestic market. To explain this pattern, we develop a real option value model where firms are heterogeneous in productivity and have to decide whether and how to sell in a foreign market where demand is risky. Selling abroad is a source of risk exposure to firms: following a negative shock, they are reluctant to exit the foreign market because they would forgo the sunk cost they paid to enter. Multinational firms are the most exposed because of the higher costs they have to pay to invest. The calibrated model is able to match both aggregate U.S. export and foreign direct investment data, and the observed cross-sectional differences in earning yields and returns.